2009
DOI: 10.1145/1462055.1462061
|View full text |Cite
|
Sign up to set email alerts
|

Classifying pretended and evoked facial expressions of positive and negative affective states using infrared measurement of skin temperature

Abstract: Earlier researchers were able to extract transient facial thermal features from thermal infrared images (TIRIs) to make binary distinction between the expressions of affective states. However, affective human-computer interaction might require machines to distinguish between the subtle facial expressions of affective states. This work, for the first time, attempts to use the transient facial thermal features to recognise a much wider range of facial expressions. A database of 324 time-sequential, visible-spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 90 publications
2
45
0
4
Order By: Relevance
“…To evoke users' stress in the experiments, there are some methods which are widely adopted, which include mental arithmetic, N-back number recall, time pressure, reading aloud, viewing affective picture or video, emotive text reading and story telling (see [6]- [9]). Among these methods, some are very useful to enable the job demands to be quantified or measured, for example mental arithmetic, N-back number recall and time pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evoke users' stress in the experiments, there are some methods which are widely adopted, which include mental arithmetic, N-back number recall, time pressure, reading aloud, viewing affective picture or video, emotive text reading and story telling (see [6]- [9]). Among these methods, some are very useful to enable the job demands to be quantified or measured, for example mental arithmetic, N-back number recall and time pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To classify stress versus non-stress conditions, besides the traditional social science research methods, the most common approaches are physiological measurements [8], [12]- [17] and www.conference.thesai.orgfacial expressions recognition [9], [18]- [23]. Although both physiological measures and facial expression recognition have high accuracy rates, but the assessments could be obtrusive, requiring additional equipment (which can be costly), and are often labour or computationally intensive [6], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Such issues were encountered during the creation of TIVs. Another issue encountered with the creation of TIVs was due to the inconsistency of size of face image of different volunteers to that of actual square grids mentioned in [24] and [34]. To overcome such issues each face image was resized.…”
Section: B Feature Extractionmentioning
confidence: 99%
“…The technique proposed by Khan et al [24] showed 66.28% of successful classification. During cross validation test and 56% of successful classification rate was reported during a person independent test [34]. If this technique is adapted into car/automobile the performance of the classifier could worsen as the input image consists of multiple faces.…”
Section: Introductionmentioning
confidence: 99%
“…Among the "informational" methods are the proposals based on measurement of biophysiological responses and their automatic translation into words that define the emotions measured (e.g. [26] and [31]). …”
Section: Framework and Modelsmentioning
confidence: 99%